Palladium-catalyzed routes to geranylated or farnesylated phenolic stilbenes: synthesis of pawhuskin C and schweinfurthin J - Singh, Mandeep; N. P. Argade (Synthesis-Stuttgart, 2012)
Starting from double MOM-protected phloroglucinol, the facile total syntheses of bioactive natural products pawhuskin C and schweinfurthin J were accomplished in good overall yields. The Heck, Stille, or Suzuki coupling reactions of two different electron-rich phenolic segments bearing geranylated or farnesylated units were involved in the decisive step. The Sonogashira coupling reaction followed by palladium-catalyzed chemo-and stereoselective cis-reduction of an alkyne unit and subsequent isomerization to give the desired natural products is also described.
Keywords: geranylated or farnesylated stilbenes; Natural products; palladium-catalyzed coupling reactions; phloroglucinol; Total synthesis

Palladium-promoted [2+2+2] cocyclization of arynes and unsymmetrical conjugated dienes: synthesis of justicidin B and retrojusticidin B - Patel, Ramesh M.; N. P. Argade (Organic Letters, 2013)
A facile synthesis of natural and unnatural arylnaphthalenes has been demonstrated via the unprecedented palladium-promoted [2 + 2 + 2] cocyclization of arynes and unsymmetrical conjugated dienes using the N-heterocyclic carbene as a ligand. The unsymmetrical dienes used herein are actually alpha-coupled acrylate - cinnamate combinations bearing two beta-positive carbons and follow the key [2 + 2 + 2] cocyclization pathway.